ANALISIS DAMPAK EKONOMI INVESTASI INFRASTRUKTUR : PENDEKATAN MODEL KOMPUTASI KESEIMBANGAN UMUM - nararia sanggrama wijaya; Wisynu Wardhana; Adventus Parulian Van Tua Simanullang; Ryan Ardany Sumarna; Akhmad Iksanuddin (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2019)
This paper discusses the impacts of infrastructure investment funded by state budget through PSN (Proyek Strategis Nasional/ National Strategic Project) on economic. It applies Dynamic Computable General Equilibrium (DCGE). The analysis was conducted through two simulations. First, it estimated the effects of PSN on certain macroeconomic indicators i.e. household consumption, private investment, export, and import. In addition, it also assessed the effects of each type infrastructure project on macroeconomic indicators. The analysis combined data from Indonesia Statistics on Indonesia Input Output Table (2010) and Indonesia Socio-economic Accounting Matrix (2008). The result shows that PSN 2015-2023 promotes Indonesia real GDP growth from 0.04 to 0.09 percentage point with the highest impact on 2024 and 2027. Furthermore, based on the investment categories, road and bridge investment are the instrument with the highest effect on GDP growth, employment, and poverty eradication. However, the majority of infrastructure project put pressure on the trade deficit, except telecommunication and energy (oil refinery). Those two sectors could narrow the trade deficit in the long term.